Pelatihan Penulisan Artikel Ilmiah bagi Mahasiswa sebagai Upaya Penguatan Kapasitas Publikasi Akademik di Lombok Barat - Galih Suryadmaja; Ilham Handika; Siti Nurjanah; Hirma Susilawati; Lalu Muazim (Jurnal Pengabdian Pada Masyarakat IPTEKS, 2026)
This community service activity aims to strengthen students’ academic publication capacity through scientific article writing training conducted in Lombok Barat. The training involved 10 students with diverse academic backgrounds and varying levels of writing experience, most of whom had limited exposure to scientific writing. The method applied was a participatory and practice-based approach, integrating conceptual explanation with direct writing exercises. The activity was conducted in one day through several stages, including needs identification, material delivery, guided writing practice, evaluation, and reflection. The results indicate a significant improvement in participants’ competencies, particularly in understanding the structure of scientific articles, developing academic arguments, and using formal academic language. All participants were able to produce initial drafts of scientific articles, which reflects an increase in both technical skills and academic confidence. Additionally, the training contributed to a shift in participants’ perceptions of scientific writing, from a complex task to a manageable and learnable process. This finding suggests that short-term, practice-oriented training can effectively enhance students’ academic literacy and support the development of sustainable academic writing skills.